Multiple criteria assessment of alternatives for built and human environment renovation - Tupenaite, Laura; Zavadskas, Edmundas Kazimieras; Kaklauskas, Arturas; Turskis, Zenonas; Seniut, Mark (Journal of Civil Engineering and Management, 2010)
The built environment is not constructed in empty space. It refers to human ‐ made spaces they live and work in and which are affected by various micro, meso and macro level factors. For this purpose, renovation decisions must be considered avoiding a narrow approach to the single projects of building renovation. Renovation of the built and human environment must be considered instead and the holistic approach used. From this perspective, decision‐making problems of renovation often involve a complex decision making process in which multiple requirements and conditions have to be taken into consideration simultaneously. This paper describes the concept of the integrated analysis of built and human environment renovation as a whole as well as presents the multiple criteria assessment of alternatives of the Bulgarian cultural heritage renovation projects. The widely known multiple criteria assessment methods SAW, TOPSIS and COPRAS and the newly developed method ARAS were used for this purpose. As a result the best project for granting was selected. First Published Online: 24 Jun 2011